Molecular Neurobiology of Depression: PET Findings on the Elusive Correlation with Symptom Severity - Smith, Donald F.; Jakobsen, Steen (Frontiers in Psychiatry, 2013)
Molecular mechanisms in the brain are assumed to cause the symptoms and severity of neuropsychiatric disorders. This review concerns the elusive nature of relationships between the severity of depressive disorders and neuromolecular processes studied by positron emission tomography (PET). The review provides a systematic account of all reports on PET and human depressive disorders that have been listed in PubMed and published since March 2009, the time of our last review on the topic. These recently published studies have concerned serotonergic, dopaminergic, muscarinic, nicotinic, and GABAergic receptors, as well as central processes dependent on monoamine oxidase, phosphodieasterase type 4, amyloid plaques, neurofibrillar tangles, and P-glycoprotein. We find, however, that reliable causal links between neuromolecular mechanisms and relief from depressive disorders have yet to be convincingly demonstrated. This situation may contribute to the currently limited use of PET for exploring the neuropathways that are currently viewed as being responsible for beneficial effects of antidepressant treatment regimes.